Orexin/Hypocretin and Histamine Cross-Talk on Hypothalamic Neuron Counts in Mice - Berteotti, Chiara; Lo Martire, Viviana; Alvente, Sara; Bastianini, Stefano; Bombardi, Cristiano; Matteoli, Gabriele; Ohtsu, Hiroshi; Lin, Jian-Sheng; Silvani, Alessandro; Zoccoli, Giovanna (Frontiers in Neuroscience, 2021)
The loss of hypothalamic neurons that produce wake-promoting orexin (hypocretin) neuropeptides is responsible for narcolepsy type 1 (NT1). While the number of histamine neurons is increased in patients with NT1, results on orexin-deficient mouse models of NT1 are inconsistent. On the other hand, the effect of histamine deficiency on orexin neuron number has never been tested on mammals, even though histamine has been reported to be essential for the development of a functional orexin system in zebrafish. The aim of this study was to test whether histamine neurons are increased in number in orexin-deficient mice and whether orexin neurons are decreased in number in histamine-deficient mice. The hypothalamic neurons expressing L-histidine decarboxylase (HDC), the histamine synthesis enzyme, and those expressing orexin A were counted in four orexin knock-out mice, four histamine-deficient HDC knock-out mice, and four wild-type C57BL/6J mice. The number of HDC-positive neurons was significantly higher in orexin knock-out than in wild-type mice (2,502 ± 77 vs. 1,800 ± 213, respectively, one-tailed t-test, P = 0.011). Conversely, the number of orexin neurons was not significantly lower in HDC knock-out than in wild-type mice (2,306 ± 56 vs. 2,320 ± 120, respectively, one-tailed t-test, P = 0.459). These data support the view that orexin peptide deficiency is sufficient to increase histamine neuron number, supporting the involvement of the histamine waking system in the pathophysiology of NT1. Conversely, these data do not support a significant role of histamine in orexin neuron development in mammals.